Tax literacy of the working youth in Portugal - Pais, Helena Maria Duarte Gomes Matos (2024)
Taxation is a fundamental component of any society since it finances public services and contributes to a country's economic development. However, the complexity of tax systems along with the lack of tax education, can lead to problems such as tax evasion, distrust in state institutions, and low tax morale. This study analyzes the impact of tax illiteracy on individuals in the early stages of their professional careers in Portugal, focusing on their tax knowledge and attitudes toward compliance. Starting from the idea that taxation should be viewed as a civic duty rather than an obligation, the study investigates how the lack of tax education in Portuguese curricula affects the relationship between citizens and tax authorities. Through an empirical study of citizens at the beginning of their professional careers in various fields, this thesis aims to analyze the predisposition of individuals to improve their tax knowledge and their perceptions of whether formal tax education would be advantageous for their personal and professional lives. The study also assesses whether tax illiteracy contributes to poor tax morale, leading to an increase in non-compliance and a weakening of the fiscal contract between the government and its citizens. It is expected that the results will allow an understanding of the potential positive effects of integrating tax education into earlier stages of the education system, in order to promote better tax compliance and macroeconomic stability in Portugal.